The typification of Variolaria discoidea Pers. - Per M. Jørgensen; Imke Schmitt (Plant and Fungal Systematics, 2023)
The type species of the lichen genus Variolaria is V. discoidea . The name is solely based on a Hoffmann (1784) illustration. To stabilize the nomenclature, we have designated a lectotype and an epitype from Germany, for which we generated molecular data. The species was formerly placed in the genus Pertusaria as P. albescens , and is presently correctly named Lepra albescens .